Marketing Prospects of Omega-3 Thornless Milkfish Agribusiness - Andi Rusdi Walinono; Rahmayati Rahmayati (Citakonsultindo, 2023)
Milkfish is a significant fish species in meeting fish consumption needs, with a production volume exceeding 158,321 tonnes in 1989. However, the presence of thorns limits its consumption in certain regions. To overcome this, a technique of processing spine-free milkfish has been developed through special treatment and cultivation in floating net cages along coastal concessions, showing promising market prospects in marine fisheries agribusiness. Compared to soft-boned milkfish products like presto milkfish, thornless Omega-3 milkfish demonstrates a 75% increase in added value, with a price increase from Rp 15,000/kg to Rp 27,500/kg, and processing costs of Rp 2,000/kg, resulting in a value increase of Rp 10,500/kg or 70%. This research aims to determine the supply and sales growth of spine-free Omega-3 milkfish and their impact on future profitability. The findings reveal that CV.Dinar Bali successfully meets the market demand for spine-free Omega-3 milkfish, with sales having a significant influence on profitability, indicating prospective opportunities for future development.